The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/7407918
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical and Machinability Characteristics of Wrought and Selective Laser Melted Ti-6Al-4V

Abstract: This research work presents a machinability study between wrought grade titanium and selective laser melted (SLM) titanium Ti6Al-4V in a face turning operation, machined at cutting speeds between 60 and 180 m/min. Machinability characteristics such as tool wear, cutting forces, and machined surface quality were investigated. Coating delamination, adhesion, abrasion, attrition, and chipping wear mechanisms were dominant during machining of SLM Ti-6Al-4V. Maximum flank wear was found higher in machining SLM Ti-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Surface quality of additive manufactured components is often found to be affected by non-uniform distribution of powders, delamination between the layers and rippling effect caused by the shear force of laser on the liquefied powder particles (Yadroitsev and Smurov, 2011). Thus, to eliminate these defects and improve the surface quality of additive manufactured components, a final touch of finish machining is always required (Shunmugavel et al, 2016a(Shunmugavel et al, , 2016b. Machining of titanium alloys is difficult and cumbersome owing to its poor thermal conductivity, work hardening and high chemical reactivity which leads to rapid tool wear and high cutting forces (Ezugwu and Wang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Surface quality of additive manufactured components is often found to be affected by non-uniform distribution of powders, delamination between the layers and rippling effect caused by the shear force of laser on the liquefied powder particles (Yadroitsev and Smurov, 2011). Thus, to eliminate these defects and improve the surface quality of additive manufactured components, a final touch of finish machining is always required (Shunmugavel et al, 2016a(Shunmugavel et al, , 2016b. Machining of titanium alloys is difficult and cumbersome owing to its poor thermal conductivity, work hardening and high chemical reactivity which leads to rapid tool wear and high cutting forces (Ezugwu and Wang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, during material deposition operations, parts are subjected to high thermal gradients, i.e. high heat and cooling rates, that lead to a higher strength and hardness of the compacted powder and consequently to higher cutting forces and tool wear rates [186]. Milton et al [187] reported that the increase of cutting forces was possibly due to microstructural discontinuities of AM components, which entailed higher wear rates and lower tool life.…”
Section: Materials and Machinabilitymentioning
confidence: 99%
“…The post-process finish machinability of SLM parts has been investigated in a number of studies [50][51][52]. Shunmugavel et al [50] found that SLM Ti-6Al-4V was more challenging to machine than its wrought counterpart. Both cutting forces and wear rates of a PVD coated tool were found to be significantly greater for the SLM material.…”
Section: Selective Laser Meltingmentioning
confidence: 99%